Angola. Bibliografia Antropológica - B. Wastiau (Outros Títulos, 2019)
From a first attempt to gather fundamental bibliography for anthropological research in Angola came out in 1983 an interim text. With the contribution of more collaborators and completing and updating this first text now comes this version of "Angola: anthropological bibliography", a working tool that we hope will be useful to many of our research colleagues. The print run has been purposely limited as an update as possible permanent. In this sense all suggestions and possible corrections will be welcomed so that all Africanists who are interested in anthropological research about Angola is available a working tool which is not exhaustive already represents very diverse information in the field of anthropological sciences. In addition to renewing its thanks to her first-hour colleague, Isilda Figueiras, I want to extend them to the researchers who have joined this work and have contributed, each with their share, to the preparation of this bibliography. [Coimbra, October 8th, 1997, M. L. Rodrigues de Areia]